Uji Aktifitas Analgetik Ekstrak Etanol Daun Pepaya (Carica papaya L.) pada Mencit Putih Jantan yang di Induksi Asam Asetat 1% - Ria Afrianti; Revi Yenti; Dewi Meustika (Jurnal Sains Farmasi & Klinis, 2014)
Analgesic activity of extract of papaya leaves (Carica papaya L.) to male mice has been evaluated. Twenty five of mice (20-30 g, 2-3 months old) were divided randomly into five groups. The first group was given sodium CMC as negative control, the second until fourth groups received ethanolic extract of Carica papaya leaves in the doses of 100, 300, and 600 mg/kgBW, respectively and the fifth group was given paracetamol 65 mg/kg BW. All interventions were administered as single dose by oral route on given day. Acetic acid 1% (w/v) was used as the pain inductor. Analgesic activity was measured by counting the percentage of writhing movements as a measure of the analgesic effect produced by each intervention. Data were analyzed with one way ANOVA to compare analgesic activity between treatment groups. The results showed that the analgesic effect of the extract on the doses of 100, 300, and 600 mg/kg BW was significantly different with control group (P